An exploratory study of brand success: evidence from the food industry - Davcik, N.; Rundquist, J. (Journal of International Food and Agribusiness Marketing, 2012)
The goal of this research is to identify drivers that influence the brand success, in order to develop a more effective business strategy. An abductive theory approach is adopted and food managers from Italy and Sweden were questioned. The authors modeled the eight correlated first-order factors, using seven independent variables and the dependent variable brand success. The variance-based structural equation modeling approach (partial least square [PLS] algorithm) have been applied. This study provides insight and empirical evidence on brand success. The findings can be employed as more effective brand strategies in a sector that has been under-investigated in academic literature and practice.